Improvement and application of a novel drainage pump of deep coalbed methane wells in south Yanchuan - WU Zhuangkun, ZHANG Honglu, CHI Yuxuan, YIN Zhonghua, ZHANG Zhuang (Youqicang pingjia yu kaifa)
In order to solve the problem of frequent well laying in the coalbed methane field in south Yanchuan due to sand production（pulverized coal）, a novel drainage pump in south Yanchuan coalbed methane well has been developed. The novel drainage pump is designed as a forced pull rod hemisphere-type seal, and the plunger assembly adopts a hollow design. The pump diameter is ø38 mm, the stroke is three meters, the stroke time ranges from one to three times per minute, and the displacement is 4.8~14.6 m3/d. The novel drainage pump is used together with hollow rod and tubing, forming a dual-channel integrated pipe string for production and cleaning. It can not only meet the normal drainage gas production, but also facilitates well flushing and discharging pulverized coal. In addition, the flushing fluid does not enter the stratum during well flushing, avoiding the pollution of the flushing fluid to the stratum and preventing the failure of the fixed valve and the pump from being stuck caused by the deposition of pulverized coal or sand in the coalbed methane field drainage well. In 2022, the novel drainage pump was applied in two wells in the south Yanchuan coalbed methane field, and since then, no fixed valve failure or pulverized coal card pump has occurred. As a result the average pump inspection period of measure wells has been extended by 285 days. Field tests demonstrate that the novel drainage pump has the dual functions of normal gas drainage and coal powder discharge through well flushing, providing a new technical support for improving the overall development level of coalbed methane field in south Yanchuan.